Monday

July 28, 2014

July 28, 2014

Posted by **Zakariya** on Saturday, February 1, 2014 at 5:34am.

- Mathematics -
**Steve**, Saturday, February 1, 2014 at 6:24amwell, we know that x = 3t+6, so use it:

4(3t+6)+3t = 9

12t+24+3t = 9

15t = -15

t = -1

so, x = 3t+6 = 3

**Related Questions**

alegbra - what are the factor of the following trinomial? 3t^2 + 19t + 6 a) (t...

Calculus AP - Evaluate the integral interval from [0 to pi] t sin(3t)dt Use ...

Calculus - I need help solving the integral of t * e^-3t dt I know that I have ...

Calculus - Simplify. State the nonpermissible values. (3t^2+3t-6/2t^2-2t-4)(4t^2...

Math - The lcm for... (1+3t) (1-9t)^2 (1-3t) Answer 9t^2 or (3t+1)(-3t+1) I'm ...

Factoring - Factor Completely: 3t^3 + 5t^2 - 12t first take out the t so you ...

Math - Using factoring by grouping, how would you factor these out. 4t^2+3t-4t-3...

math - Using factoring by grouping, how would you factor these out. 4t^2+3t-4t-3...

Math Help - 1) 1+cos(3t)/ sin(3t) + sin(3t)/( 1+ cos(3t))= 2csc(3t) 2) sec^2 2u-...

Check my CALCULUS answers please! - Any short explanation for things I got ...